Somatic experiencing: using interoception and proprioception as core elements of trauma therapy - Payne, Peter; Levine, Peter A.; Crane-Godreau, Mardi A. (Frontiers in Psychology, 2015)
Here we present a theory of human trauma and chronic stress, based on the practice of Somatic Experiencing® (SE), a form of trauma therapy that emphasizes guiding the client's attention to interoceptive, kinesthetic and proprioceptive experience. SE™ claims that this style of inner attention, in addition to the use of kinesthetic and interoceptive imagery, can lead to the resolution of symptoms resulting from chronic and traumatic stress. This is accomplished through the completion of thwarted, biologically based, self-protective and defensive responses, and the discharge and regulation of excess autonomic arousal. We present this theory through a composite case study of an SE treatment; based on this example, we offer a possible neurophysiological rationale for the mechanisms involved, including a theory of trauma and chronic stress as a functional dysregulation of the complex dynamical system formed by the subcortical autonomic, limbic, motor and arousal systems, which we term the core response network (CRN). We demonstrate how the methods of SE help restore functionality to the CRN, and we emphasize the importance of taking into account the instinctive, bodily based protective reactions when dealing with stress and trauma, as well as the effectiveness of using attention to interoceptive, proprioceptive and kinesthetic sensation as a therapeutic tool. Finally, we point out that SE and similar somatic approaches offer a supplement to cognitive and exposure therapies, and that mechanisms similar to those discussed in the paper may also be involved in the benefits of meditation and other somatic practices.